A Novel Resolution of Diabetes: C-C Chemokine Motif Ligand 4 Is a Common Target in Different Types of Diabetes by Protecting Pancreatic Islet Cell and Modulating Inflammation - Chang, Ting-Ting; Lin, Liang-Yu; Chen, Jaw-Wen (Frontiers in Immunology, 2021)
Systemic inflammation is related to hyperglycemia in diabetes mellitus (DM). C-C chemokine motif ligand (CCL) 4 is upregulated in type 1 & type 2 DM patients. This study aimed to investigate if CCL4 could be a potential target to improve blood sugar control in different experimental DM models. Streptozotocin-induced diabetic mice, Leprdb/JNarl diabetic mice, and C57BL/6 mice fed a high fat diet were used as the type 1 DM, type 2 DM, and metabolic syndrome model individually. Mice were randomly assigned to receive an anti-CCL4 neutralizing monoclonal antibody. The pancreatic β-cells were treated with streptozotocin for in vitro experiments. In streptozotocin-induced diabetic mice, inhibition of CCL4 controlled blood sugar, increased serum insulin levels, increased islet cell proliferation and decreased pancreatic interleukin (IL)-6 expression. In the type 2 diabetes and metabolic syndrome models, CCL4 inhibition retarded the progression of hyperglycemia, reduced serum tumor necrosis factor (TNF)-α and IL-6 levels, and improved insulin resistance via reducing the phosphorylation of insulin receptor substrate-1 in skeletal muscle and liver tissues. CCL4 inhibition directly protected pancreatic β-cells from streptozotocin stimulation. Furthermore, CCL4-induced IL-6 and TNF-α expressions could be abolished by siRNA of CCR2/CCR5. In summary, direct inhibition of CCL4 protected pancreatic islet cells, improved insulin resistance and retarded the progression of hyperglycemia in different experimental models, suggesting the critical role of CCL4-related inflammation in the progression of DM. Future experiments may investigate if CCL4 could be a potential target for blood sugar control in clinical DM.